Knowledge, Attitude and Practice on Regenerative Endodontics among Endodontists of Nepal (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Regenerative Endodontics is one of the most fascinating development in modern dentistry. Since Endodontists are the first providers of this type of dental treatment, it is essential to learn their knowledge, attitude and practice of these procedures. Aim: This online questionnaire-based study was conducted amongst Endodontists practicing in Nepal with the aim to learn their knowledge, attitude and practice of regenerative endodontic procedures.MATERIALS AND METHODS: A cross-sectional study was conducted among Endodontists in Nepal. In total 65 Endodontists participated in this study. The questionnaire was distributed to the participants using the available electronic measures. Descriptive statistical analyses were performed on the responses given by Endodontists using SPSS Statistical Software package (version 21.0).RESULTS: A total of 20 questions were included in this study. Out of the responses analyzed, 100% (n=65) had come across the term regenerative endodontics. Respondents had good knowledge about the sources of dental stem cells (87.3%, n=55). A high percentage (98.4%, n=62) of respondents strongly recommended regenerative therapy to be incorporated into dentistry. Among the participants of this study, 87.1% (n=54) had a belief that regenerative endodontic treatment could serve as the alternative treatment option to dental implant.CONCLUSIONS: The Endodontists practicing in Nepal had sound knowledge about regenerative endodontic procedures. They were enthusiastic in practicing regenerative endodontics and interested in stem cell therapy. It’s a high time to uplift the regenerative endodontic procedure from simple revascularization via blood clotting to more advanced procedure.